A MODEL OF COMMUNITY ECONOMIC EMPOWERMENT BY THE GERAKAN MENULIS HARAPAN (GMH) IN THE CITY OF SURABAYA - Rizzaki, Adam Ramadhan; Faizah, Siti Inayatul (International Journal of Research -GRANTHAALAYAH, 2020)
Dolly localization is the largest prostitution area in Southeast Asia, located in Putat Jaya, Sawahan District, Surabaya City. On June 18 2014 the official Dolly localization was closed. After Dolly’s closure, the Gerakan Menulis Harapan (GMH) had an extraordinary role of importance to help former commercial sex workers and affected citizens restore the economy in a halal manner with an economic empowerment model. This article aims to analyze the economic empowerment model carried out by GMH on the Community in Putat Jaya Village, Surabaya City. The method used in this article is a qualitative research method with a case study approach. The conclusion of this article is the empowerment of the creative economy through the Guidance program of GMH Surabaya in doing stakeholder synergy with various parties, namely the media, government and donors, as well as the people of Surabaya, especially members of the fostered GMH. To run the GMH coaching program, it receives financial assistance from donors where to carry out economic empowerment through various activities, namely assistance, training and marketing.